2018
DOI: 10.3390/ijms19123883
|View full text |Cite
|
Sign up to set email alerts
|

2′-Fluoro-Pyrimidine-Modified RNA Aptamers Specific for Lipopolysaccharide Binding Protein (LBP)

Abstract: Lipopolysaccaride binding protein (LBP), a glycosylated acute phase protein, plays an important role in the pathophysiology of sepsis. LBP binds with high affinity to the lipid part of bacterial lipopolysaccaride (LPS). Inhibition of the LPS-LBP interaction or blockage of LBP-mediated transfer of LPS monomers to CD14 may be therapeutical strategies to prevent septic shock. LBP is also of interest as a biomarker to identify septic patients at high risk for death, as LBP levels are elevated during early stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…However, ribose modifications such as 2 0 -deoxy or 2 0 -amino, 2 0 -fluoro confer resistance to ribonucleases. 46 Moreover, nucleobase modifications, such as 5-fluoro, impart protection against ribonucleases. 47 We synthesized 2 0 dFC-modified 5FU-EGFR aptamers and monitored their influence on tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, ribose modifications such as 2 0 -deoxy or 2 0 -amino, 2 0 -fluoro confer resistance to ribonucleases. 46 Moreover, nucleobase modifications, such as 5-fluoro, impart protection against ribonucleases. 47 We synthesized 2 0 dFC-modified 5FU-EGFR aptamers and monitored their influence on tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Lbp can act as a lipid transfer protein to transfer LPS to the CD14/TLR4 receptor complex on immune cells, thereby enhancing the immune response to LPS [ 46 ]. It has been reported that high levels of Lbp in the serum of septic patients attenuated the inflammatory response of macrophages and monocytes to LPS [ 47 ]. In addition to systemic infection, infectious and allergic lung inflammation can also lead to increased serum Lbp levels [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS binds to lipopolysaccharide binding protein (LBP), and LBP can promote the binding of LPS and CD14 to form LPS/LBP/CD14 complex. 31 The LPS/LBP/CD14 complex binds to TLR4 and finally stimulates the production of NF-κB and activating protein 1 (Activated Protein 1) and interferon regulatory factor (IRF), which in turn promotes the release of pro-inflammatory cytokines TNFα, IL-1β and IL-6. 32,33 Previous studies have found that the TLR4/NF-κB pathway is widely involved in LPS-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%